HUBUNGAN POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK BALITA USIA 1-3 TAHUN DI POSYANDU DADAP INDAH KABUPATEN TANGERANG TAHUN 2021 - Solihati, Solihati; Rusmita, Ikka; Sari, Rina Puspita (Nusantara Hasana Journal, 2022)
The future of a nation lies in the hands of its young generation, including those who are still toddlers, toddlers as a golden age or "golden age" i.e. if at that time childrenÂ  under five are not properly nurtured, then the child will experience emotional, social, mental, intellectual and moral development disorders which can later affect their attitudes and behavior in the future, The World Health Organization (WHO) in 2018 reported that the prevalence data for children under five with growth and development disorders was 28.7% and Indonesia was included in the third country with the highest prevalence in the Southeast Asia region/Sout ZZh-East Asia Regional (SEAR). Research Objectives: to find out the relationship between parenting styles and gross motoric development of children under five at the Posyandu Dadap Indah, Tangerang Regency in 2021. This type of research is quantitative using a descriptive correlation design with a cross sectional approach, the sampling technique used is total sampling based on the data. at the Dadap Indah Posyandu, Tangerang Regency in 2021, so that 44 respondents were obtained. The data analysis technique used is the Chi square test using SPSS 20. The research shows that the dominant parenting pattern of positive parenting is 35 respondents (79.5%), and gross motor development of children according to 33 respondents (75%) with Chi-square statistical test analysis p-value 0.018 <a 0.05, the results of the analysis of the Spearman correlation coefficient with a significant value (2-tailed) = 0.017 < 0.005, the correlation value of 0.358% is categorized as moderate correlation. There is a relationship between parenting patterns and gross motor development of toddlers aged 1-3 years at the Dadap Indah Posyandu, Tangerang Regency.